Five-kilometers time trial: preliminary validation of a short tests for cycling performance evaluation - Dantas, J. L.; Pereira, G.; Nakamura, F. Y. (Asian Journal of Sports Medicine, 2015)
Background: The five-kilometer time trial (TT5km) has been used to assess aerobic endurance performance without further investigation of its validity.